Tinjauan Maqasid Syariah Terhadap Kalender Islam Global - Syamsul Anwar (University of Muhammadiyah Sumatera Utara, 2019)
This writing deals with Islamic International Calendar from the perspective of shariah objectives. Representing one of the most important parts of the Islamic Legal Theory (Uṣūl al-Fiqh), shariah maqasid are discussed widely in the modern times, both concerning their doctrines as well as their application in dealing with other matters of shariah. After clarifying the meaning of shariah objectives and Islamic International Calendar including its concept, principles, qualifications, and parameters, the writer proceed to examine some questions such as is there any objective in shariah doctrines regarding calendar, if the answer is positive what kind of calendars is in line with shariah objebtives and does phisical seeing of the moon represent one of shariah maqāṣid? The writer comes to several conclusions one of which is that, in general, Islamic International Calendar has a close relation to Islamic law objectives.